2016
DOI: 10.1371/journal.pone.0165955
|View full text |Cite
|
Sign up to set email alerts
|

Fenugreek Seed Powder Nullified Aluminium Chloride Induced Memory Loss, Biochemical Changes, Aβ Burden and Apoptosis via Regulating Akt/GSK3β Signaling Pathway

Abstract: Alzheimer's disease (AD) is the most common form of dementia that mainly affects the cognitive functions of the aged populations. Trigonella foenum-graecum (L.) (fenugreek), a traditionally well utilized medicinal plant ubiquitously used as one of the main food additive worldwide, is known to have numerous beneficial health effects. Fenugreek seed extract could be able to inhibit the activity of acetylcholinesterase (AChE), a key enzyme involved in the pathogenesis of AD, and further shown to have anti-parkins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 66 publications
(84 reference statements)
5
31
0
Order By: Relevance
“…After 24 h the rat was placed in the light chamber again and the time taken to enter the dark chamber was recorded as step-through latency. If the animal did not enter the dark chamber within a 3-min test period, the test was terminated and the step-through latency was noted as 180 sec ( Prema et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h the rat was placed in the light chamber again and the time taken to enter the dark chamber was recorded as step-through latency. If the animal did not enter the dark chamber within a 3-min test period, the test was terminated and the step-through latency was noted as 180 sec ( Prema et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, each and every rat was placed individually again in the light chamber and the time taken by them to enter into the dark chamber was considered as step-through latency. If the rat did not enter the dark chamber within a 5-minute test period, the test was ceased and the step-through latency was noted as 300 seconds (23).…”
Section: Passive Avoidance Taskmentioning
confidence: 99%
“…Alzheimer's disease [AD]) are associated with chronic inflammation, oxidative stress (Mayeux 2010;Ahmad et al 2018), progressive cognitive deficits and changes in neuro-behavioural pattern (Jellinger 2013). AD is linked with memory deficit and tau protein (Prema et al 2017). There is need for new drug discovery to combat this menace as it is reported that 75% of the thirty-six million people worldwide affected with dementia are estimated to be AD patient, and it is predicated that 1 in 85 people will be affected by 2050 (Bhattacharya et al 2014).…”
Section: Introductionmentioning
confidence: 99%